2008
DOI: 10.1111/j.1751-0813.2008.00349.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen‐induced responses in lymphocytes from platypus, the Tasmanian devil and the eastern barred bandicoot

Abstract: For the first time, we report the normal cellular response of the platypus, the Tasmanian devil and the eastern barred bandicoot to a range of commonly used mitogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Despite the apparent absence of the Ig-like domain in the platypus Ig- α protein, the platypus Ig- α TAM appears to be functional. Immunological studies in the platypus have demonstrated mitogen induced B-cell proliferation [89], as well as B-cell intracellular signaling activation [90, 91], both of which require Ig- α /Ig- β heterodimers with functional ITAMs [92, 93]. The remainder of the amino acids in the Ig- α TAM region are exactly the same across all species tested in the mammalian class (YEGLNLDDCSMYEDI) [6].…”
Section: Resultsmentioning
confidence: 99%
“…Despite the apparent absence of the Ig-like domain in the platypus Ig- α protein, the platypus Ig- α TAM appears to be functional. Immunological studies in the platypus have demonstrated mitogen induced B-cell proliferation [89], as well as B-cell intracellular signaling activation [90, 91], both of which require Ig- α /Ig- β heterodimers with functional ITAMs [92, 93]. The remainder of the amino acids in the Ig- α TAM region are exactly the same across all species tested in the mammalian class (YEGLNLDDCSMYEDI) [6].…”
Section: Resultsmentioning
confidence: 99%
“…Culture conditions yielding the best viability were selected for the mitogen stimulation assay. Cells were stimulated with phytohemaglutinin from Phaseolus vulgaris (PHA-M; 10, 25 or 50 µg/ml; Sigma), based on concentrations reported for other species [ 3 , 9 , 25 , 34 , 35 ].…”
Section: Main Textmentioning
confidence: 99%
“…21 Results of T-cell proliferation assays revealed that devils have a relatively robust mitogen-induced response. 31,72 Of particular note was the finding that devils affected with DFTD had similar mitogen-induced responses as their disease-free counterparts, suggesting that immune suppression, at least at the level of lymphocyte proliferation, does not explain susceptibility to DFTD.…”
Section: Cell-mediated Immune Response Of the Tasmanian Devilmentioning
confidence: 99%